Smart Cities and IoT: Integration, Security, and Sustainability - T.R. Premila (AG Volumes, 2025)
The fast development of urbanization has increased the implementation of Smart City programs led by the Internet of Things (IoT). This review paper examines the application of IoT technologies within the smart city systems with the consideration of security and sustainability. IoT enabled systems help to collect data in real time, manage infrastructure intelligently and provide more public services in transportation, energy, waste management, environmental monitoring and public safety. The research paper is a synthesis of the current research to analyze enabling technologies (5G, edge computing, AI-based analytics, blockchain, and low-power wide-area networks) to support smart city ecosystems. Also noted in it are key issues such as data privacy threats, cybersecurity issues, complexity of the system, interoperability, and sustainability. This paper presents an in-depth insight into the implementation of the secure and scalable integration of IoT to enable resilient, efficient, and clean urban development in the intelligent cities of tomorrow by studying modern literature and real-life examples.